Atrial Septal Aneurysms and Supraventricular Arrhythmias: The Role of Atrial Electromechanical Delay. Issue 10 (3rd March 2015) - Russo, Vincenzo; Rago, Anna; Di Meo, Federica; Papa, Andrea Antonio; Ciardiello, Carmine; Cristiano, Anna; Calabrò, Raffaele; Russo, Maria Giovanna; Nigro, Gerardo
<x xml:space="preserve">Abstract</x> Background Paroxysmal supraventricular arrhythmias (SVAs) frequently occur in patients with atrial septal aneurysm (ASA). The aim of the current study was to evaluate the electrocardiographic (P‐wave duration and dispersion) and echocardiographic (atrial electromechanical delay, AEMD) noninvasive indicators of atrial conduction heterogeneity in healthy ASA subjects without interatrial shunt and to assess the AEMD role in predicting the SVAs onset in this population. Materials and Methods One hundered ASA patients (41 males, mean age of 32.5 ± 8 years) and 100 healthy subjects used as controls, matched for age and gender, were studied for the occurrence of SVAs during a 4‐year follow‐up, through 30‐day external loop recorder (ELR) monitoring performed every 3 months. ASAs were diagnosed by transthoracic echocardiography based on the criteria of a minimal aneurismal base of ≥15 mm and an excursion of ≥10 mm. Intra‐AEMD and inter‐AEMD of both atria were measured through tissue Doppler echocardiography. P‐wave dispersion (PD) was carefully measured using 12‐lead electrocardiogram (ECG). Results Compared to the healthy control group, the ASA group showed a statistically significant increase in inter‐AEMD, intra‐left AEMD, maximum P‐wave duration, and PD. Dividing the ASA group into 2 subgroups (patients with or without SVAs), the inter‐AEMD, intra‐left AEMD, P max, and PD were significantly higher in the subgroup with SVAs compared to the subgroup without SVAs. There were significant good correlations of intra‐left AEMD and inter‐AEMD with PD. A cutoff value of 40.1 msec for intra‐left AEMD had a sensitivity of 82% and a specificity of 83% in identifying ASA patients at risk for SVA. Conclusion Our results showed that the echocardiographic AEMD indices (intra‐left and inter‐AEMD) and the PD were significantly increased in healthy ASA subjects without interatrial shunt. PD and AEMD represent noninvasive, inexpensive, useful, and simple parameters to assess the SVAs' risk in ASA patients.